KOMPARASI PENDIDIKAN ISLAM K.H. AHMAD DAHLAN DAN MUHAMMAD FETHULLAH GÜLEN - Mohamad Ali (Universitas Muhammadiyah Surakarta, 2016)
Islamic education is considered only oriented to the hereafter alone, teach rituals and develop a defensive posture and formisme paradigm. On the other hand, Islamic education is faced with the phenomenon of discontinuity which marked the waning value of respect for the basic values and ethics, such as honesty, discipline, tolerance. This Problem is what ignited K.H. Ahmad Dahlan (1868-1923) and Muhammad Fethullah Gülen (1838 - ...) strengthening Islamic education. This study aims to understand the concepts, practices, and comparative Islamic education K.H. Ahmad Dahlan and Muhammad Fethullah Gülen. This type of research is the study of literature with historical and philosophical approach.The results show: first, the concept of Islamic education K.H. Ahmad Dahlan stressed intregration of religious sciences and the modern sciences, tolerance, open to modernity and perfection of mind (intellect); for Fethullah Gülen education is a manifestation of Allah, which emphasizes ethics, science, and theology. Secondly, the common the sharing concept between the two are at: ideas, foundation, educational goals and teaching methods. Third, while the point of difference lies in the educational materials, dormitory educational models (boarding school) and implementing a system of moving class.